Patologiska förändringar och säsongsmässiga variationer i testiklar från svenska brunbjörnar (Ursus arctos) - Lennse, Jenni (2009)
Functioning reproductive organs are essential for the survival of a species. The reproductive system is very sensitive to exposure of chemical substances of anthropogenic origin. Humans release great amounts of chemical substances to the environment by our means of life and these substances have been proved to have a negative effect on the reproductive ability of different vertebral classes. In the polar bear (Ursus maritimus) a declined reproductive ability as an effect of decreased testosterone levels and decreased testicular size has been connected to the presence of high levels of organohalogenic compounds like PCBs. Although the Swedish brown bear (Ursus arctos) is not as carnivorous as its close relative the polar bear it is still exposed to environmental. The brown bear is a seasonal breeder with a short breeding season in late spring and early summer and has a natural fluctuation in testosterone levels as well as size and morphology of the testes during the year. In this study testicles from 51 Swedish brown bears that were shot during the hunting season in 2007 were examined macroscopically. Testes and epididymis from twelve of these bears have been examined microscopically for the presence of pathological changes and seasonal changes in morphology. For comparison testes from nine bears that died in spring was examined macroscopically and microscopically.